Understanding the Risk Factors and Diagnosis of Cervical Cancer: A Review of Vaccination and Drug Delivery Materials - Shubhanshu Goel; Monika Singh; Shubh Deep Yadav; Moumita Barman (Journal of Sustainable Materials Processing and Management, 2024)
Globally cervical cancer is a significant one of the major cause of death in women. One-third of the total new cases arises of this disease in women across the globe. It is generally spread by papillomavirus (HPV). It may happen due to having multiple sex partner relationship, uses of distinct contraceptives methods, smoking as well as dietary factors responsible for cervical cancer. Now a days, cervical cancer exposure has currently spread rapidly. So, this study aims to explore epidemiology, causes, diagnosis, current treatment method to overcome this disease affected individuals. Initially in cervical cancer affected individual, no symptom is appeared but as ever it affects any other organs of body, it can produce various symptoms like pelvic, abdominal pain, vaginal bleeding as well as gynecological infection. So, it is necessary that at ages of 9 to 15 years individuals should be vaccinated. Currently, three HPV vaccines are approved for different cervical cancer targets, namely Gardasil, Cervarix, and Gardasil, which target HPV6, HPV11, HPV16, HPV 18 HPV31, HPV33, HPV45, HPV52, and HPV58 respectively.  Especially HPV E6 and E7 genes showed a great potential for treating cervical cancer. Simultaneously radiotherapy, immunotherapy, chemotherapy and distinct drug delivery method are helpful to destroy cancer cell in cervical cancer affected individuals.